USING OF FIRST GENERATION OF Hl ANTIHISTAMINES As ALTERNATIVE OF LOCAL ANESTHETIC IN ODONTOLOGIC USE IN ANESTHESIA INFILTRATIVE TECHNICS. EXPERIMENTAL STUDY IN ANIMALS - Rodríguez Alfaro, Miguel (2004)
The presence of adverse drug reactions with local anesthetics takes us to the search of effective alternatives to this drugs. 60 albino rabbits divided into 6 groups were submifted to infiltrative anesthetic technique in the maxilla with lidocaine, mepivacaine, bupivacaine, chlorpheniramine and dimenhidrinate, in front of sodium chloride 0,9%. The pain threshold belzavior was evaluated with electrical stimulation from Ruhnkorff s bobbin behind the drllg application and comparison between groups was made. The wlzite llsed drugs elevated the pain threshold, with a better response of lidocaine. Both local anesthetics and antihistamine drugs produced an effective local anesthesia, without tissue damage.